Laser protection with optical limiting by combination of polymers with dyes. Issue 10 (12th October 2018) - Hege, C. S.; Muller, O.; Merlat, L.
ABSTRACT: Lasers are becoming more and more common and can damage eyes and sensors, so arise the need for efficient protection. A possibility is the use of filters with optical limiting abilities. Optical limiting leads to a reduced transmittance of these filters above a certain light energy. Solid‐state optical limiting filters consist frequently of poly(methyl methacrylate) (PMMA). Using dyes is an often used way to provide optical limiting qualities to polymers. PMMA does not offer the possibility to attach the dye covalently to the polymer chain. Poly(lactide), also a transparent polymer, has so far not been used for filters for optical limiting. Its polymerization mechanism offers a simple possibility to a covalent binding of the dyes, by using them as initiator. This should be, like the attaching of big side groups to dyes, a possibility to increase stability of dyes against aggregation. Hybrids out of polymers and dyes and filters thereof could be produced. The polymers were analyzed by nuclear magnetic resonance, gel permeation chromatography, and nonlinear optical measurements. Including azophloxine leads to an attenuation of the laser beam in the range of 10 −3 and Eosin B even to 10 −5 . The eosin sample shows a two magnitudes better attenuation then usual guest–host systems like poly(methyl acrylate) with carbon nanotubes. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47150. Abstract : These polymers were used as filters for laser protection by optical limiting. This method leads to an attenuation of the transmission of the filter at high light energy so it cannot reach eyes or sensors. With these polymers, a very efficient attenuation of the transmission could be reached.